PSIKOLOGI PEMASARAN DI ERA KOMUNIKASI DIGITAL - Lia Kurniawati; Dewi Untari; Muhammad Irsyad Raspati (Fakultas Hukum Universitas Malikussaleh, 2022)
The mix between psychology in marketing activities known as marketing psychology is still a new thing for marketers in Indonesia. The use of marketing psychology is very useful for marketers to sell their products/services. Even though this is still new, marketing psychology has developed very rapidly to be used by marketers along with the current development of digital communication. For example, if in the past many marketers used demographic and geographical approaches to segment their markets, now many marketers use a psychographic approach through advertising sentences (copywriting) or with other psychological approaches that marketers deliberately study first. In an effort to expand the market, many marketers use a mix of demographic, geographic and psychographic approaches. Marketing psychology is very helpful for managers, especially for marketing managers to solve many marketing problems, especially those related to their consumers. Consumers are human beings whose one aspect is the soul. Humans are different from products because humans have souls and feelings that are so complex. The emergence of marketing psychology helps marketing managers to understand their customers and then they will in turn know how they can better attract consumers to grow sales of their products/services. Even this is used in the current era of digital communication where consumer data is very easy to obtain and directly confirmed by potential consumers so that consumer psychological data can be easily analyzed.